ANALISIS NITRAT REDUKTASE SECARA “IN-VIVO” PADA TANAMAN JAGUNG, KACANG HIJAU, TEBU, UWI DAN CABAI - Edy Suryono (UIN Sunan Kalijaga Yogyakarta, 2016)
Nitrate Reductase (NR) is an enzyme that catalyzes the nitrate to nitrite and are inducible because its activity can be enhanced by the addition of substrate. Plants obtain nitrogen by absorbing nitrate or ammonia ions present in the soil, the absorption of ionic compounds are used to form various nitrogen compounds such as proteins. The purpose of this study are : (1) measure, analyze the activity of nitrate reductase (ANR) maize plant leaves, green beans, sugar cane, chili, uwi and chili in “in-vivo”, (2) determining the value of ANR with the manufacture of standard curve NO2 (compound product) from the leaves of corn plants, green beans, sugar cane, uwi and chili, (3) learn Nitrate Reductase Activity (ANR) pepper plants were not cultivated, and fertilized with (NaNO3): 0.1, 0.2 and 0.4, and (5) determining the value of ANR with the manufacture of standard curve NO2 (compound product) from pepper plants were fertilized and not fertilized and the chilli plant organs. The tools used in the study of measurement ANR in vivo, the distribution of nitrate reductase and the physiologic effects of plants on the ANR is: a razor blade, the base to create a wedge, scales semi- analytic, tubes dark (movie), test tubes, micropipette, pipettes measure (5 ml), vortex and spectrophotometers. Materials used in the study in vivo measurement of ANR is a chili plant leaves, maize, uwi, sugarcane, green beans, 5M NaNO3, NaNO2 0,6M, 0.1 pH 7.5 phosphate buffers; 0.02 % NED (Napthyediamine), 1 % SA (sulfanilamide) in 3N HCl and distilled water. Materials used to study the distribution of nitrate reductase and plant physiological effect to ANR is the chili plants before flowering, during flowering and fruiting moment, while khemikalia ANR together with lab measurements in vivo. The results showed that: (1) The pepper plant is a plant that has activity Nitrate Reductase highest among five tested plants, while the plants uwi have nitrate reductase activity low, (2) long incubation can reduce the activity of Nitrate Reductase from five plant species tested, (3) based on the organs of plants, the highest measurements on leaves, based on the plant age measurements the ANR highest at seedling, (4) based on the leaf position, the ANR measurment of highest at section near the base, and (5) based on fertilization of NaNO3, the ANR measurement of highest at a concentration of 0.2 M.